Introduction: MMPs, ADAMs/ADAMTSs Research Products to Achieve Big Dream - Okazaki, Isao; Nabeshima, Kazuki (Anti-Cancer Agents in Medicinal Chemistry, 2012)
Matrix metalloproteinases (MMPs) are known to participate in cancer invasion and metastasis. Copious research on MMPs and their inhibitors has promoted the understanding of the mechanisms of cancer invasion and metastasis as well as the development of effective drugs for cancer treatment. This review discusses the classification of MMPs and tissue inhibitors of metalloproteinases (TIMPs) in relation to tumor growth and invasion mechanisms via signal transduction, followed by the possibilities for cancer treatment. The review focuses especially on the development of anti-cancer agents in the field of MMP science.
Keywords: cancer cellinvasion